2016
DOI: 10.1002/cne.24113
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐ and region‐specific expression of depression‐related protein p11 (S100a10) in the brain

Abstract: P11 (S100a10), a member of the S100 family of proteins, has widespread distribution in the vertebrate body, including in the brain, where it has a key role in membrane trafficking, vesicle secretion and endocytosis. Recently, our laboratory has shown that a constitutive knockout of p11 (p11 KO) in mice results in a depressive-like phenotype. Furthermore, p11 has been implicated in major depressive disorder (MDD) and in the actions of antidepressants. Since depression affects multiple brain regions, and the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 94 publications
(157 reference statements)
2
30
0
Order By: Relevance
“…p11 in hippocampal cells is essential in mediating the response to antidepressants (12). In this brain region, p11 is highly enriched in PV and cholecystokinin GABAergic interneurons (13). In cholecystokinin cells, p11 regulates the surface levels of the 5-HT 1B serotonergic receptor to initiate the response to antidepressants, an effect mediated by disinhibition of PV cells (14).…”
mentioning
confidence: 99%
“…p11 in hippocampal cells is essential in mediating the response to antidepressants (12). In this brain region, p11 is highly enriched in PV and cholecystokinin GABAergic interneurons (13). In cholecystokinin cells, p11 regulates the surface levels of the 5-HT 1B serotonergic receptor to initiate the response to antidepressants, an effect mediated by disinhibition of PV cells (14).…”
mentioning
confidence: 99%
“…Yet, we have seen some marker genes differentially expressed in only one of the clusters. For instance, radial glial markers s100a10 (Milosevic et al, 2017) and cx43 (Duval et al, 2002) are expressed in only one of the dRGC, mRGC and vRGC clusters (dRGC1, mRGC1, vRGC1; Dataset S1B). Since these genes are associated with a more progenitor state of the radial glia, we can speculate that s100a10+/cx43+ clusters could represent a radial glial state that is more progenitor-like.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have shown that the depression disorder is regulated by the 5-HT1B receptor. Recently, it was documented that S100A10 is potentially able to be involved in the regulation of depression [76] through its distribution in the brain that is relative to the depression-like behavioral phenotype [76] or interacting with 5-HT1B receptor [77]. S100A10 distributes widely in the vertebrate body containing the brain in which the expression of S100A10 is subsistent in some neurons and nonneuronal cells as well as is discrepant within disparate regions.…”
Section: The Role Of S100a10 In Non-tumor Diseasesmentioning
confidence: 99%